Bio-efficacy of plant extracts for management of purple blotch disease of onion (Allium cepa) - MEENA, R.P. (Indian Phytopathology, 2012)
Botanical pesticides are of the indispensable components of integrated pest management and are gaining importance due to safety point of view, were tested to manage purple blotch of onion caused by Alternaria porri, under in vivo and in vitro condition. The pathogen is most destructive and limiting factor for higher productivity in the crop.Â Poisoned food technique (plant extracts amended PDA medium) used to screen the different extracts in vitro at the concentrations of 1.0, 2.0 and 5.0 percentage; to measure percent inhibition of radial growth, sporulation and spore germination. The plant extracts evaluated for A. porri, it was observed that maximum inhibition 97.05% of mycelial growth was recorded in Palmarosa oil amended culture at 5% concentration followed by Ocimum sanctum 95.58% at the same concentration over check. Whereas Eucalyptus, Palmarosa and Ocimum sanctum oils showed minimum sporulation intensity 0.16, 0.26 & 0.39 x 103/ml, respectively. O. sanctum found most effective in reducing the spore germination (75.58%) under in vitro condition. In the in vivo condition maximum reduction 46.47% of disease incidence was recorded in Push sprayed plot followed by 44.75%, Perfekt and 44.23 % in Polyalthia longifolia over the check. The onion bulbs yield also observed higher in lesser infected plots.